2013
DOI: 10.3390/ma6010265
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation of Low-Level Airborne 2-Propanol and Trichloroethylene over Titania Irradiated with Bulb-Type Light-Emitting Diodes

Abstract: This study examined the photocatalytic oxidation of gas-phase trichloroethylene (TCE) and 2-propanol, at indoor levels, over titanium dioxide (TiO2) irradiated with light-emitting diodes (LED) under different operational conditions. TiO2 powder baked at 450 °C exhibited the highest photocatalytic decomposition efficiency (PDE) for TCE, while all photocatalysts baked at different temperatures showed similar PDEs for 2-propanol. The average PDEs of TCE over a three hour period were four, four, five, and 51% for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…These photocatalytic degradations have been carried out in the presence of natural sunlight or a mercury vapor lamp [16,17]. However, energy-efficient light emitting diodes (LEDs) have recently been used as an alternative light source for the photocatalytic degradation of various pollutants present in water [18,19] and in air [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…These photocatalytic degradations have been carried out in the presence of natural sunlight or a mercury vapor lamp [16,17]. However, energy-efficient light emitting diodes (LEDs) have recently been used as an alternative light source for the photocatalytic degradation of various pollutants present in water [18,19] and in air [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis has drawn a lot of attention in environmental application in recent years [ 1 ]. Removal of pollution from the environment using TiO 2 as the photocatalyst is one of the research focuses due to TiO 2 ’s innocuity, chemical stability, cheapness, commercial availability, reusability, as well as the vast reactivity towards wide variety of pollutants [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantage of LEDs over traditional ultraviolet light sources, LEDs have recently been employed for the removal of gases from air. It has been reported that various organic air pollutants, such as formaldehyde, glucose, isopropyl methyl phosphonofluride, dimethyl sulfide, 2-propanol, aceton vapors, tolune, and trichloroethylene, were degraded using different LEDs. , …”
Section: Photocatalysis Using Light Emitting Diodesmentioning
confidence: 99%